Bottom-Up or Top-Down, both Required Commitment - Sukmono, Renny; Budiarsih, Riani (Management Institute Faculty of Economics Universitas Andalas, 2019)
One of the strategies of the Ministry of Finance is to encourage good budget management top-down by including the element of budget realization in setting the Key Performance Indicator (IKU). Determining the target budget of a year is top-down, while for budget withdrawal plan (prognosis budget) each month of the year is set bottom-up. This Prognosis budget is used as the target to be achieved by the working unit. The budget achievements show how much effort the work unit has made in achieving the targets they set themselves. Budget achievement is a comparison between the realization of the budget achieved and the target set. The smaller the budget achievement, it can be said that the commitment of the work unit to achieve the target is still low. In 2016, there are still a number of echelon I who still have a lot to do to increase this commitment. This is proved by the varying budget achievements that can be achieved by the echelon I. There is a work unit that has a very low budget achievement which is until the third quarter it only reaches 20% of the total budget, on the other hand, there is a work unit that is able to exceed the set target. Echelon I units that still have homework include Echelon I